2013
DOI: 10.1186/1471-244x-13-120
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination in relation to parenthood reported by community psychiatric service users in the UK: a framework analysis

Abstract: BackgroundExperienced discrimination refers to an individual’s perception that they have been treated unfairly due to an attribute and is an important recent focus within stigma research. A significant proportion of mental health service users report experiencing mental illness-based discrimination in relation to parenthood. Existing studies in this area have not gone beyond prevalence, therefore little is known about the nature of experienced discrimination in relation to parenthood, and how is it constituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 33 publications
0
31
0
1
Order By: Relevance
“…Previous qualitative studies have often identified the same groups and settings as the most common sources of discrimination: family members, healthcare professionals and employers . A small number of studies have looked at specific settings – for example hospitals – or circumstances – for example parenting . The range of behaviour types identified is also fairly consistent across the literature, including the expression of prejudicial views (such as dangerousness), overprotection, having views discounted or disbelieved, being avoided, structural discrimination and experiencing physical abuse or neglect .…”
Section: Introductionmentioning
confidence: 84%
“…Previous qualitative studies have often identified the same groups and settings as the most common sources of discrimination: family members, healthcare professionals and employers . A small number of studies have looked at specific settings – for example hospitals – or circumstances – for example parenting . The range of behaviour types identified is also fairly consistent across the literature, including the expression of prejudicial views (such as dangerousness), overprotection, having views discounted or disbelieved, being avoided, structural discrimination and experiencing physical abuse or neglect .…”
Section: Introductionmentioning
confidence: 84%
“…Jeffery et al . () reported 23% of individuals receiving community‐based psychiatric services felt discriminated against for starting a family and 28% in their role as a parent.…”
Section: Introductionmentioning
confidence: 99%
“…If children stay in the family, parents may be confronted with prejudices and discrimination, given the stigma individuals with mental illness who are parents often face. Jeffery et al (2013) reported 23% of individuals receiving community-based psychiatric services felt discriminated against for starting a family and 28% in their role as a parent.…”
Section: Introductionmentioning
confidence: 99%
“…The association between unmet accommodation needs and unmet childcare needs also requires special attention. Adult mental health services rarely consider that their clients could be parents and that their illness is likely to impact on their children's mental health (David, Styron, & Davidson, ; Diaz‐Caneja & Johnson, ; Jeffery et al, ). For instance, the perception of succeeding or failing as a mother can have a significant impact on her well‐being as well as her ability to recover (Nicholson, ).…”
Section: Discussionmentioning
confidence: 99%